Complete nucleotide sequence of the gene for a surface protein antigen of Streptococcus sobrinus. - Tokuda, M (1991)
The complete nucleotide sequence of the gene for a cell surface protein antigen (SpaA) of Streptococcus sobrinus MT3791 (serotype g) was determined. The spaA gene consisted of 4,698 bp and coded for a protein of 170,202 Da. A putative signal peptide was found in the amino-terminal end of the protein. A potential promoter sequence and a putative Shine-Dalgarno sequence preceded the open reading frame. Two internal repeating amino acid sequences were present in SpaA. One repeating region, located in the amino-terminal region, was rich in alanine, and the other, located in the central region, was rich in proline. The molecular structure of SpaA was very similar to that of the surface protein antigen of Streptococcus mutans.